Vaccination and its impact on healthcare utilization in two groups of vaccinated and unvaccinated patients with COVID‐19: A cross‐sectional study in Iran between 2021 and 2022 - Erfan Kharazmi; Mohsen Bayati; Ali Majidpour Azad Shirazi (Health Science Reports, 2024)
Abstract Background and Aims One of the main responsibilities of health systems impacted by the global Coronavirus disease 2019 (COVID‐19) pandemic, where the first case was discovered in Wuhan, China, in December 2019, is the provision of medical services. The current study looked into the impact of vaccination on the utilization of services provided to COVID‐19 patients. Methods This study was conducted in Iran between 2021 and 2022, utilizing a cross‐sectional research design. The research team collected data on the utilization of provided services and the number of COVID‐19 vaccines administered to 1000 patients in Iran through a random sampling approach. The data were analyzed with statistical methods, including the mean difference test, and multiple linear regression. Results Regression estimates show that after controlling for confounding variables like age, type of admission, and comorbidities, vaccination reduces the utilization of healthcare services in the general majority of services. The study's results reveal a fall in COVID‐19 patients' utilization of services, specifically in patients administered two or three doses of the vaccine. However, the reduction is not statistically significant. Regression models are in contrast to univariate analysis findings that vaccination increases the mean utilization of healthcare services for COVID‐19 patients in general. Comorbidities are a crucial factor in determining the utilization of diagnostic and treatment services for COVID‐19 patients. Conclusion Full COVID‐19 vaccination and other implementations, including investing in public health, cooperating globally, and vaccinating high‐risk groups for future pandemics, are essential as a critical response to this pandemic as they reduce healthcare service utilization to alleviate the burden on healthcare systems and allocate resources more efficiently.